DIGITAL LITERACY PRACTICES IN ELEMENTARY EDUCATION: CHALLENGES AND OPPORTUNITIES FOR POST-PANDEMIC CLASSROOM LEARNING TRANSFORMATION - Rafidhah Hanum; Fakhrul Rijal; Muhammad Zulhairi Zubairi (SENSEI RESEARCH CENTER, 2023)
Digital literacy has become a core competence in elementary education as schools move from emergency remote instruction to more stable post-pandemic learning. Although children are increasingly familiar with digital devices, their everyday use of technology does not automatically develop critical, creative, safe, and academically meaningful literacy. This article aims to synthesize how digital literacy is practiced in elementary classrooms, identify recurring challenges, and formulate opportunities for strengthening post-pandemic classroom learning. The study used a narrative literature review of international peer-reviewed studies on digital literacy, digital competence, technology integration, primary education, and digital pedagogy. The literature was analyzed thematically by focusing on the forms of practice, implementation barriers, and pedagogical possibilities relevant to young learners. The synthesis shows that digital literacy practices in elementary education are reflected in five interrelated areas: digital information searching and evaluation, multimodal content creation, digital communication, technology-supported collaboration, and responsible online behavior. The main challenges include unequal access to devices and connectivity, uneven teacher digital competence, students' limited critical evaluation skills, entertainment-oriented technology habits, and insufficient family mediation. However, post-pandemic classrooms also offer opportunities to integrate digital literacy across subjects, design blended and inquiry-based activities, strengthen teacher professional development, and build school-family partnerships for safe and productive technology use. The article concludes that digital literacy should be positioned not as a technical supplement but as a pedagogical framework for inclusive, ethical, and future-oriented elementary education.